Implementation of Monsakun Problem-Posing to Enhance Elementary School Students' Conceptual Understanding of Mathematics in Indonesia - Rico Valentino; Munir Munir; Herbert Siregar (Brilliance: Research of Artificial Intelligence, 2025)
This study was conducted to develop Monsakun, a web-based Problem Posing learning platform, through the Research and Development (R&D) method using the 4D model: Define, Design, Develop, and Disseminate. The main objective of this research is to create an interactive and effective learning tool that enhances students' ability to understand and apply concepts through systematic Problem Posing activities. The study responds to existing challenges in Problem Posing-based learning, which is often perceived as less engaging and insufficient in nurturing students' critical thinking and creativity. The research procedures included a comprehensive needs analysis, prototype design, product development, and testing for effectiveness. User experience was measured using the User Experience Questionnaire (UEQ) and System Usability Scale (SUS). The results indicated that Monsakun received an "Excellent" rating in terms of attractiveness, efficiency, accuracy, and stimulation. However, improvements are needed in clarity and novelty, particularly regarding user guidance and the integration of more innovative features. With an average SUS score of 86, the platform demonstrated a high level of usability, suggesting strong user acceptance and satisfaction. Overall, the findings show that Monsakun is effective in supporting students' learning outcomes, offering an engaging and user-friendly experience. Moreover, the R&D approach used in this study has proven successful in guiding the development of impactful educational technology, thus contributing meaningfully to the advancement of web-based learning media.